Static Data Flow Analysis of PL/I Programs with the PROBE System - Sarraga, Ramon F. (IEEE transactions on software engineering, 1984)
An experimental data flow analyzer for PL/I programs has been implemented within the PROBE system developed at the GM Research Laboratories. PROBE is an experimental software package that examines the internal structure of PL/I programs in order to expose error-prone design and programming features. This paper describes 1) the algorithms and data structures used by the data flow analyzer, 2) the salient aspects of PL/I usage in the analyzed production-level programs, and 3) the results of the data flow analysis.